Preventive effect of Polyherbal mixture against Rifampicin and Pylorus ligation-Induced Gastric Ulcers and liver necrosis in Rats - Abhijeet shashikant kulkarni; C. Vijaya Raghavan; D. M Patil (International Journal of Phytomedicine, 2013)
Antitubercular drug is produced hepatotoxicity is major drawback of an effective treatment of treatment of tuberculosis. In this paper we review the incidence, pathology and clinical features of antituberculosis drug-induced hepatotoxicity, discuss the metabolism and mechanisms of toxicity of Rifampicin, and describe risk factors and management of antituberculosis drug induced hepatotoxicity, the antiulcer activity was assessed by determining and comparing the ulcer index in the test drug groups with that of the vehicle control and standard Omeprazole. In case of pylorus ligation induced ulcers, the polyherbal mixture showed significant reduction of ulcers in a dose dependent manner. The parameters taken to assess antiulcer activity were % inhibition ulcer index. The results indicated that polyherbal mixture significantly (p<0.001) decreased the % inhibition ulcer index as well as hepatoregenrative action.